PSYCHOLOGICAL RESILIENCE AND ITS RELATIONSHIP TO JOB SATISFACTION AMONG A SAMPLE OF HEALTH PRACTITIONERS AT TAIF GOVERNORATE HOSPITALS - Omar Ali alkhaldi; Salman Ateyah althagafi; Homayed Mohammad Alsawat; Khalid Mohammad alhumayyani; Saad Sead aljuaid; Saeed Ali almalki; Ameera Aoda alzhrani; Saleh Jameel alotaibi; Adnan Mousa almalki; Mohammad Abed althagafi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This study aimed to know the relationship between psychological resilience and job satisfaction among a sample of health practitioners in Taif Governorate hospitals. The study sample consisted of (159) health practitioners in those hospitals, where the questionnaire was used as a tool to collect data from the study members. The study results showed that the presence of a medium level of dimensions of psychological resilience (after emotional the mental dimension, the social dimension) among health practitioners at Taif governorate hospitals, while the presence of an average level of job satisfaction among health practitioners at Taif governorate hospitals. In addition, the results indicated a statistically significant relationship between all dimensions (emotional dimension, mental dimension, social dimension) and satisfaction occupational health practitioners at Taif governorate hospitals. In light of the results, the study recommended the need for hospital management in Taif governorate to seek an interest in developing psychological resilience among health practitioners, as it is closely related to the level of job satisfaction and its achievement. Preparing awareness programs to provide psychological and moral support to health practitioners in hospitals, and setting plans to overcome their job satisfaction obstacles.